Kidney allograft interstitial fibrosis and tubular atrophy (IFTA) due to specific causes: : Bacterial infection/pyelonephritis (Pakistan Journal of Kidney Diseases, 2022)
Not applicable
Keywords: IFTA; Kidney Transplant; acute rejectio; bacterial infection; cyclosporine toxicity